An experimental investigation of the effect of defect shape and orientation on the burst pressure of pressurised pipes. (November 2018) - Al-Owaisi, Sultan; Becker, Adib A.; Sun, Wei; Al-Shabibi, Abdullah; Al-Maharbi, Majid; Pervez, Tasneem; Al-Salmi, Hussain
Abstract: The burst pressure of commonly used ductile steel pipes in oil and gas industries, i.e. X52 and X60, is measured under internal pressure loading. The pipes were machined with circular and boxed defects at different orientations to simulate actual metal loss defects. Defect shapes and orientations were investigated in detail to study how they affect the failure behaviour of interacting defects. The experimental burst pressure results were compared with those obtained using existing analytical methods from Design Codes. Comparison of the results showed conservatism in the existing analytical methods which may potentially lead to unnecessary plant shutdowns and pipe repairs. The outcome of the experimental tests revealed that the shapes of the defects have very small influence on the defect interaction behaviour. The burst tests interestingly showed that the defect orientation has an important effect on defect interaction. Defects oriented in the hoop and diagonal directions showed no defect interaction even when spaced by a distance of one wall thickness, while defects oriented in the longitudinal directions showed that defects interact even when the spacing is up to six wall thickness but the interaction fades away for defects spaced at longer distances. Highlights: Experimental 31 pipe burst tests with machined metal loss defects analysed The effects of defect shape, orientation and interaction are investigated Results compared with existing analytical methods from Design Codes Degree of conservatism in the existing design codes discussed Results show that defect orientation has an important effect on defect interaction